Uma ferramenta de estimativa de custos para o desenvolvimento distribuído de software - Pagno, Rodrigo Tomaz (2010)
In search of competitive advantage and higher profits, companies now are trying improve their way of producing software. One of the solutions is the distribution of software development. The cost estimates of software development have always been a challenge due to their large uncertainties and differences between the cost of the final estimated value. This challenge becomes even greater when we refer to the distributed development of software, where geographically dispersed teams interact together to develop software products. In this situation, this paper presents a tool to support managers during the realization of cost estimates for software projects. To this end, the tool takes into account the cost accounting of each team and implements three different ways of estimating software products; i) estimation by analogy (which completed projects which have similarities in certain features are found), ii) the use of models empirical (in which mathematical equations are combined with some variable characteristics to estimate projects), iii) estimate by an expert (in which experts estimate projects). Thus, the tool provides support to the project manager to realize cost estimates for distributed development of software.